2020
DOI: 10.18203/2394-6040.ijcmph20205694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severity of diabetic retinopathy on quality of life in type 2 Indian diabetic patients

Abstract: Background: Diabetes mellitus is a global public health challenge of 21st century and diabetic retinopathy is a common complication of long standing and poorly controlled diabetes which hampers patient’s physical, social and emotional well-being leading to poor quality of life. Objective was to study the correlation between severity of diabetic retinopathy and quality of life in type II DM patients.Methods: A prospective, longitudinal and observational study was conducted in 120 patients of type II diabetes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recent longitudinal and observational study showed that QoL significantly decreases with aggravation of DR severity from mild NPDR to PDR. [ 57 ] Furthermore, a cross-sectional study showed that vision-related functional burden is significantly greater in patients with severe NPDR or PDR versus those with no retinopathy. [ 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal and observational study showed that QoL significantly decreases with aggravation of DR severity from mild NPDR to PDR. [ 57 ] Furthermore, a cross-sectional study showed that vision-related functional burden is significantly greater in patients with severe NPDR or PDR versus those with no retinopathy. [ 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics [ 4 ], out of the 463 million individuals diagnosed with diabetes worldwide, approximately 30% also experience DR. This disease demonstrates a progressive nature, highlighting the importance of timely diagnosis and treatment to prevent permanent vision loss [ 8 ]. DR can be categorized into two subtypes: nonproliferative DR (NPDR) and proliferative DR (PDR).…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics [4], out of the 463 million individuals diagnosed with diabetes worldwide, approximately 30% also experience DR. This disease demonstrates a progressive nature, highlighting the importance of timely diagnosis and treatment to prevent permanent vision loss [8]. DR can be categorized into two subtypes: non-proliferative DR (NPDR) and proliferative DR (PDR).…”
Section: Introductionmentioning
confidence: 99%